LISTENING MATERIALS IN ENGLISH TEXTBOOK: QUALITY REVIEW - Shabrina Ikbar; Hermansyah Hermansyah; Evi Rosmiyati (Esteem Journal of English Education Study Programme, 2023)
The objective of this study was to assess the quality of listening materials in the English textbook "Work in Progress: Buku SMA," published by Pusat Perbukuan in 2022. The research focused on evaluating the effectiveness of the listening materials based on a set of criteria developed by Zhang (2020). The research question formulated was, "What is the quality of the listening materials in the English textbook?" The methodology employed in this research was content analysis. The data were collected through document analysis, and the researcher organised and classified the data into eight criteria. After categorising the data according to the seven criteria, the researcher analysed the data chapter by chapter. Finally, conclusions were drawn based on the findings. According to the results, out of the eight criteria, five were fully met, one was partially met, and two were not met. Therefore, it can be concluded that the listening materials in the English textbook "Work in Progress" are deemed "effective."